2019
DOI: 10.3390/computation7020026
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Chemical Space of Cytochrome P450 Inhibitors Using Integrated Physicochemical Parameters, Drug Efficiency Metrics and Decision Tree Models

Abstract: The cytochrome P450s (CYPs) play a central role in the metabolism of various endogenous and exogenous compounds including drugs. CYPs are vulnerable to inhibition and induction which can lead to adverse drug reactions. Therefore, insights into the underlying mechanism of CYP450 inhibition and the estimation of overall CYP inhibitor properties might serve as valuable tools during the early phases of drug discovery. Herein, we present a large data set of inhibitors against five major metabolic CYPs (CYP1A2, CYP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 130 publications
(208 reference statements)
0
6
0
Order By: Relevance
“…Initially, the concept of drug efficiency metrics has been applied for the selection of efficient modulators against true drug targets [49]. Recently, drug efficiency metrics were used to select the highly efficient inhibitors of CYP450 isoforms which represents an anti-target [22]. Only five CYP3A4 inhibitors (Figure 2) out of the large data set of 2747 compounds (Table S1) showing the defined thresholds (Materials and Methods and Section S1) of activity (IC 50 : 0.1–38 nM), clogp (1.98–2.88), lipophilic efficiency (LipE) (5.44–7.65), ligand efficiency (LE) (0.21–0.40 kcal mol −1 HA-1) and fit quality ≥1 (Figure S1a,b) were selected for further docking and molecular dynamics studies to probe the binding hypothesis within the active site of CYP3A4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, the concept of drug efficiency metrics has been applied for the selection of efficient modulators against true drug targets [49]. Recently, drug efficiency metrics were used to select the highly efficient inhibitors of CYP450 isoforms which represents an anti-target [22]. Only five CYP3A4 inhibitors (Figure 2) out of the large data set of 2747 compounds (Table S1) showing the defined thresholds (Materials and Methods and Section S1) of activity (IC 50 : 0.1–38 nM), clogp (1.98–2.88), lipophilic efficiency (LipE) (5.44–7.65), ligand efficiency (LE) (0.21–0.40 kcal mol −1 HA-1) and fit quality ≥1 (Figure S1a,b) were selected for further docking and molecular dynamics studies to probe the binding hypothesis within the active site of CYP3A4.…”
Section: Resultsmentioning
confidence: 99%
“…For the identification of highly potent inhibitors of CYP3A4, a large dataset of CYP3A4 inhibitors was extracted from the ChEMBL database () [93] using a filtering criteria of IC 50 ≤ 100 µM. After removal of duplicates and fragments the remaining data set of 2747 compounds was subjected to LipE- and LE calculations [22] as described by Hopkins et al [49]. A brief detail of LipE and LE calculations of the CYP3A4 inhibitors has been provided in the Supplementary Materials (SM) (Section S1, Figure S1a,b and Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytochrome P450 enzymes are inherently lipophilic and thus have a predilection for lipophilic substrates [ 21 , 22 , 23 , 24 , 25 ]. It has been hypothesized that molecular weight and lipophilicity represent key physiochemical characteristics useful in predicting CYP binding affinity [ 21 , 26 , 27 , 28 ]. In further exploring this hypothesis, we examined CYP inhibitors deposited in the ChEMBL database to further illustrate the relationship between molecular weight, lipophilicity, and the IC 50 of various major cytochromes ( Figure 2 ).…”
Section: Physiochemical Propertiesmentioning
confidence: 99%
“…significantly affect the pharmacokinetics, drug interactions and clinical efficacy and side effects of flavonoids [5]. Studies have shown that phase II metabolites are the main form of flavonoids that existed in vivo , while phase I drug metabolizing enzymes, alike cytochrome P450 (CYP) and etc., play a weak role in the internal disposal for flavonoids [6]. But it can be significantly affected by the efficient coupling of drug metabolizing enzymes with efflux transporters [7].…”
Section: Introductionmentioning
confidence: 99%